Pengaruh Fasilitas Concordia Lounge Terhadap Kepuasan Penumpang Bandar Udara di Yogyakarta Internasional Airport - Andika Yusuf Maulana; Nuning Agustina Ambarsari (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of the study was to find out and analyze whether there was any effect the concordia lounge facility had on passenger satisfaction. Data collection is carried out by questionnaires conducted in the concordia lounge of Yogyakarta International Airport airport to obtain primary data. The research method uses an associative method with a quantitative approach with a simple linear regression analysis which can be obtained with a result of Y = - 1.724 + 1.416 X and the correlation coefficient value R = 0.926. Then the coefficient of determination ???? 2 is obtained at 85.8% while 14.2% is influenced by other factors. Based on the t test obtained a result of t_hitung>t_tabel (21,003 ˃ 1,993), which means there is a positive and significant influence between concordia lounge (X) facilities on passenger satisfaction (Y).